Gross count multi-spectra analysis of weak activity sources amid elevated background and various shielded conditions - Fischer, Joseph Christian, author; Brandl, Alexander, advisor; Johnson, Thomas E., committee member; Lindsay, James, committee member (Colorado State University. Libraries, 2018)
Current methods to detect low activity radiological sources in areas with elevated or changing background may be insufficient for assessing real-time events. Background radiation fluctuates throughout the day, which thwarts the effectiveness of decision thresholds (y*) extrapolated from long background count times. However, decision thresholds calculated from a string of spectral measurements can be used to optimize the decision threshold (y*) at which count rates statistically exceed background. The goal of this project is to apply a frequentist string data analysis tool to real-time gross count sodium iodide (NaI) spectra under varying background radiation and shielding conditions. A sodium iodide scintillator is utilized with the ProSpect acquisition software to acquire gross count data for analysis of the source detection efficiency under varying background and shielding conditions. A series of measurements is taken using short count times, and assessed using Receiver Operating Characteristics (ROC) curves. The best combination of N measurements, with n events individually exceeding a discriminator threshold, is determined using true positive rates from the generated ROC curves. Ideally, the optimized combination of n exceedances of the discriminator threshold in N measurements discerns weak signals from elevated background, while minimizing false positive events.